The Effects of Critical Thinking Disposition, Perception of Others and Empathy on Communication Competency among Students Majoring in Nursing (Medico Legal Update, 2020)
Background/Objectives: This study seeks to identify correlations among critical thinking, perception of others and communication competencyamong nursing school studentsMethod/Statistical Analysis: Survey respondents were 1st, 2nd, 3rd and 4th year students majoring in nursing at three universities of Chung Nam and Chung Buk who understood the objectives of the study and who gave their consent on participation.Findings: The critical thinking of subjects scored 3.27(1~5), their perception of others scored 3.35(1~5), empathy scored 3.15(1~5) and communication skills was 3.34(1~5). Variables affecting respondents’ communication competencywere critical thinking disposition 27.5%(?=.42, p